Biogas production from three-phase olive mill solid waste in lab-scale continuously stirred tank reactor. (15th March 2019) - Al Afif, Rafat; Linke, Bernd
Abstract: Biogas production of three-phase olive mill solid waste (3POMSW) was studied in lab-scale continuously stirred tank reactors (CSTR) at organic loading rates of 1.5–2.0 g VS L −1  d −1 and temperatures of 35 and 55 °C. To acclimate microorganisms to 3POMSW the start-up phase was performed under thermophilic and mesophilic conditions for 40 days. In order to improve the biogas yield, the enzyme MethaPlus ® was added and its effect was investigated. Results indicate that thermophilic processing has a higher biogas yield by 8% compared to mesophilic conditions, but there was no significant difference in methane yield. Under thermophilic conditions, addition of the enzyme to 3POMSW resulted in a significant increase in methane yield by 10%. Under mesophilic conditions, the enzyme did not have a significant effect on biogas yield or reactor performance. The quality of biogas for all experiments was sufficient. Long-term experimentation indicated the beginning of reactor failure.